Temporalis Tendon Transposition for Dynamic Facial Reanimation following Radical Oncologic Resection. (23rd August 2013) - Nagel, Thomas H.; Howard, Brittany E.; Donald, Carrlene B.; Crujido, Lisa R.; Hayden, Richard E.
Abstract : Objectives: Report a patient series in which a temporalis tendon transposition was performed for facial paralysis following radical oncologic resection. 1) Describe the modifications in technique of temporalis tendon transfer associated with concurrent cancer resection. 2) Evaluate the effect of complex defects and their reconstruction on facial reanimation outcomes. Methods: Retrospective review of 10 patients who underwent orthodromic temporalis tendon transposition for dynamic facial reanimation of their facial paralysis following radical cancer resection from January 2010 through February 2013. Data was collected for parotid malignancy, defect composition, reconstructive details, postoperative course, complications, and outcomes. Results: All patients underwent radical parotidectomy with facial nerve sacrifice and resection of adjacent soft and/or bony tissue for parotid malignancy. Complex defects included cutaneous loss necessitating concurrent flap reconstruction (n=5), partial or total temporal bone resection (n=6), and mandibulectomy (n=2). All patients underwent dynamic reanimation with temporalis tendon transposition through a nasolabial incision. Facial reanimation was performed at the same time as the resection in 6 cases and in a delayed setting in 4 cases. There was no difference in outcomes in these two patient groups. Due to tumor involvement, six resections included sacrifice of the internal maxillary artery without resultant compromise of the temporalis transfer. During the follow‐up period, all patients had improved facial symmetry at rest and developed voluntary motion with post‐procedure facial training therapy. Conclusions: Temporalis tendon transposition is a reliable, straightforward option for dynamic facial reanimation in the oncologic patient. Radical resection does not prohibit using this technique.